Development of a versatile [68Ga]Ga-FAPI-46 automated synthesis suitable to multi-elutions of germanium-68/gallium-68 generators - Paty, Louis-Paul; Degueldre, Simon; Provost, Claire; Schmitt, Camille; Trump, Laura; Fouque, Julien; Vriamont, Charles; Valla, Frank; Gendron, Thibault; Madar, Olivier (Frontiers in Chemistry, 2024)
Gallium-68-labeled FAPI-46 has recently been proposed as a novel positron emission tomography imaging probe to diagnose and monitor a wide variety of cancers. Promising results from several ongoing clinical trials have led to a soaring demand for this radiotracer. Typical [68Ga]Ga-FAPI-46 labeling protocols do not cope with multiple generator elutions, leaving radiopharmacies unable to scale-up the production and meet the demand. Here, we propose a robust and efficient automated radiosynthesis of [68Ga]Ga-FAPI-46 on the Trasis miniAllinOne synthesizer, featuring a prepurification step which allows multiple generator elutions and ensures compatibility with a wide range of gallium-68 generators. Our approach was to optimize the prepurification step by first testing five different cationic cartridge chemistries. Only the strong cationic exchange (SCX) cartridges tested had sufficient affinities for quantitative trapping of >99.9%, while the weak cationics did not exceed 50%. Packaging, rinsing, or flowing of the selected SCX cartridges was not noticeable, but improvements in fluidics managed to save time. Based on our previous development experience of [68Ga]Ga-FAPI-46, radiolabeling optimization was also carried out at different temperatures during 10 min. At temperatures above 100°C, radiochemical yield (RCY) > 80% was achieved without significantly increasing the chemical impurities (<5.5 μg mL-1). The optimized sequence was reproducibly conducted with three different brands of widely used generators (RCY >88%). A comparison with radiosyntheses carried out without prepurification steps was also conclusive in terms of RCY, radiochemical yield, and chemical purity. Finally, high-activity tests using elutions from three generators were also successful for these parameters. [68Ga]Ga-FAPI-46 was consistently obtained in good radiochemical yields (>89%, n = 3), and the final product quality was compliant with internal specifications based on European Pharmacopoeia. This process is suitable for GMP production and allows scaling-up of routine productions, higher throughput, and, ultimately, better patient care.